Acylhydrazone functionalized benzimidazole-based metallogel for the efficient detection and separation of Cr3+. Issue 41 (12th October 2018) - Yao, Hong; Wang, Jiao; Zhou, Qi; Guan, Xiao-Wen; Fan, Yan-Qing; Zhang, You-Ming; Wei, Tai-Bao; Lin, Qi
Abstract : The novel gelatorBM could self-assemble into the supramolecular organogelBMG and form the metallogelBMG-Fe with Fe 3+ in glycerol.BMG-Fe exhibits superior absorption, removal capacity and selective detection for Cr 3+ . Abstract : Chromium(iii ) is a kind of microelement and can be converted to the more toxic chromium(vi ), which is a carcinogen, by redox cycling. Thus, the development of novel materials for the detection and removal of Cr 3+ is a very important issue. A novel metallogel chemosensor (BMG-Fe ) based on functionalized benzimidazole (BM ) and Fe 3+ was constructed, which could fluorescently detect and separate Cr 3+ . The detection limit ofBMG-Fe for Cr 3+ is 2.62 × 10 −8 M, and it exhibited high sensitivity and selectivity for Cr 3+ . Meanwhile, the absorbing percentage ofBMG-Fe for Cr 3+ is 96.36%, indicating a high separation rate. Interestingly, the sensitivity and ingestion capacity ofBMG-Fe for Cr 3+ are better than that of the simple organogel (BMG ). So, the metallogelBMG-Fe could be utilized for the efficient removal of heavy metal ions from waste water.